Ethical Analysis of the Pregnant Women's Decision-Making Process about Congenital Anomalies Detected during the Prenatal Period in Turkey - Gamze Özbek Güven; Neyyire Yasemin Yalım (Galenos Publishing House, 2021)
Objectives:The study has been focused on how the women make sense of what they experience in the decision-making process about continuing or terminating the pregnancy after the prenatal diagnosis. In this process, the expression of the problems experienced by those who lived and their decisionmaking experiences have been analyzed in terms of medical ethics.Method:The study was carried out as a qualitative field research in order to achieve the aim of it. During the study, after prenatal diagnosis, in-depth interviews were conducted with women who decided to continue the pregnancy and women who decided to terminate the pregnancy. The data obtained from the in-depth interviews were evaluated by thematic analysis method.Results:As a result of the evaluation of the data obtained in this study, some important information that can be used as a basis for justification in discussions on terminating the pregnancy after prenatal diagnosis, which is a problem in medical ethics, were obtained. At the same time, it was also observed that the decision on terminating the pregnancy is a personal and difficult decision and the personal factors and a person's world of values play a determinant role in this decision.Conclusion:In our study, the findings revealed that the moral mindset of individuals was the main determinant in the decision to be made on sensitive and difficult issues, such as the termination of pregnancy.